A case of forecast-based technology evaluation and its implications. (25th January 2011) - Kim, Byoung Soo
As the importance of a national catch-up strategy, science and innovation policy, and forecasting the future is emphasised, a more advanced method of technology evaluation is needed for the emerging countries including South Korea. The methodology of forecast-based technology evaluation introduced by KISTEP consists of the Delphi survey, data analysis of papers and patents, technology growth curve fitting, and so on. Each nation's technological changes can be compared by using technology growth curves fitted from the data of the Delphi survey. With these results, R&D decision-makers can forecast the near future from a technology-level perspective.